2015
DOI: 10.1021/acs.nanolett.5b03024
|View full text |Cite
|
Sign up to set email alerts
|

Kapitza Resistance between Few-Layer Graphene and Water: Liquid Layering Effects

Abstract: In this section we present the details on simulations we performed. Initially N + 2 graphene layers of size L × L are placed along z axis with d = 3.35Å spacing between each other. Followed is the water block of size L × L × W and N + 2 more graphene layers of the same size. The resulting system is mirrored with respect to a XY plane and shifted along Z such that distance d between graphene layers of the original system and its symmetric image is maintained. The schematic of the setup is shown in Fig. 1 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
169
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(196 citation statements)
references
References 41 publications
23
169
3
1
Order By: Relevance
“…From the aspect of thermal transport, it is well known that interfacial thermal (Kapitza) resistance occurs between different materials, and an effective method to reduce Kapitza resistance is to introduce a thermal coupler . The carbon shell can act as a thermal coupler and facilitate the heat transfer from the Au core to the surrounding water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the aspect of thermal transport, it is well known that interfacial thermal (Kapitza) resistance occurs between different materials, and an effective method to reduce Kapitza resistance is to introduce a thermal coupler . The carbon shell can act as a thermal coupler and facilitate the heat transfer from the Au core to the surrounding water.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2, the calculated Raman peak intensity is obviously stronger in the Au-C core-shell structure due to the plasmon-phonon coupling, indicating that hot electron-phonon interactions are enhanced. From the aspect of thermal transport, it is well known that interfacial thermal (Kapitza) resistance occurs between different materials, [38] and an effective method to reduce Kapitza resistance is to introduce a thermal coupler. [39,40] The carbon shell can act as a thermal coupler and facilitate the heat transfer from the Au core to the surrounding water.…”
Section: Structural Design Based On Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for every single contact, physical limitations in phonon transfer have to be taken into account, leading to a highly inefficient heat transfer across the nanoparticles network that characterize nanocomposites materials 15 . Compatibilization between nanoparticles or between nanoparticles and matrix have been suggested by various authors [16][17][18] as a possible solution to decrease interfacial resistance. A chemical compatibilization is typically obtained by the functionalization of nanoplatelets with molecules able to build chemical bridges towards the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies supported the importance of Brownian motion for the enhanced thermal conductivity of nanofluids [35,36], there are other researchers against it [37,38]. As for the liquid layer at the liquid/particle interface, molecular dynamic simulations [39][40][41][42] discovered water density fluctuation near the solid surface representing the liquid layer and could explain the thermal behavior such as temperature jump on the surface, while some studies [43][44][45] indicated that the liquid layer might not influence the thermal behavior of nanofluids. In addition, Keblinski et al [44] found that ballistic heat transport still could not explain the anomalous thermal conductivity enhancements either.…”
Section: Introductionmentioning
confidence: 99%